VISION OF THE LANGUAGE IN A POEM OF YOLANDA WESTPHALEN’S UNIVERSO EN EXILIO (1984): RHETORICAL ANALYSIS OF “6” - Salvador Arauzo, Gaby (2020)
This article seeks to show the theme of language in Yolanda Westphalen’s poetry Universo en exilio (1984). For this, we will analyze poem “6”, wich shows us, from a philosophical perspective, the criticism of the possibility of language (and, specifically, of communication itself). In this way, we seek that at the end of the article we can better explain the configuration of the idea about the complexity of the language that this collection of poems has.